Philosophical Views of I.Yusupov - Orazbayev , Arislanbay (Indonesian Journal Publisher, 2025)
Ibrahim Yusupov, a distinguished poet of Uzbekistan and Karakalpakstan, is renowned for his philosophical poetry, which deeply connects the themes of homeland, human nature, and personal emotions. This article explores the way Yusupov’s works address the emotional and philosophical dimensions of life, with a particular focus on his portrayal of his homeland, the Motherland, and his relationship with his mother. Through a close analysis of his poems, such as